GOLDEN PROFILOGRAPHY: AESTHETICS OF FACIAL PROPORTIONS IN A GROUP OF STUDENTS FROM THE FACULTY OF DENTISTRY OF THE UNIVERSITY OF CUENCA - Aguirre Valle, Sugey Anaela; Apolo Carrión, Yanderin Nicol; Auquilla Bravo, Flavia Camila; Jara Sangurima, Joselyne Nayelly; Sauca Chalán, Nancy Pilar; Bravo Calderon, Manuel Estuardo (RECISATEC - REVISTA CIENTÍFICA SAÚDE E TECNOLOGIA - ISSN 2763-8405, 2024)
The approach to the harmony of a facial profile involves multiple studies, of which in this study the golden ratio and profiling are analysed to see the aesthetics and facial pattern of the patients. Golden Profilography is defined as the drawing of the vertical facial profile of aesthetic proportions obtained by means of the golden section from a photograph of the facial profile. Material and methods. The Golden Profilography is a photograph of the facial profile with aesthetic proportions obtained from measurements of the patient's facial profile enlarged to life size, from which we take the measurement corresponding to the vertical nasal axis divided by the golden section. Results. We carried out this study in students of the Seventh Cycle of the Faculty of Dentistry of the University of Cuenca from different regions of the country, who underwent a radiographic examination in order to determine their profile, clearly for academic purposes. A total of 27 students. All of them were profiled in the same way using the aforementioned software such as Nemocast. Conclusions. The facial profile obtained by the selected software verifies the golden aesthetics and it is evident that in a group of students a higher index of a mesofacial profile is reflected, which is historically known as a normal profile.